“I Haven’t Told Other People. I Want to Keep My Dignity”: HIV Related Stigma Among the Elderly in Uganda - Nakasujja N; Nakigudde J; Lwanga IB; Sezibera V (HIV/AIDS: Research and Palliative Care)
Noeline Nakasujja,1,* Janet Nakigudde,1,* Isaac Byangire Lwanga,2,* Vincent Sezibera3,* 1Department of Psychiatry, Makerere University College of Health Sciences, Kampala, Uganda; 2Infectious Diseases Institute, Makerere University College of Health Sciences, Kampala, Uganda; 3Centre for Mental Health, National University of Rwanda, Kigali, Rwanda*These authors contributed equally to this workCorrespondence: Noeline Nakasujja, Department of Psychiatry, Makerere University College of Health Sciences, P.O. Box 7072, Kampala, Uganda, Email drnoeline@yahoo.comPurpose: Numerous studies focus on stigma, HIV disclosure’s impact on treatment compliance, especially in younger groups. Limited research exists about older individuals. We therefore explored issues related to disclosure of HIV status and HIV-related stigma in the elderly.Patients and Methods: This was an exploratory qualitative study, employing Straussian Grounded Theory. We enrolled individuals aged 60 and above, living with HIV and receiving care from the Infectious Disease Institute, Uganda. We conducted 4 focus group discussions to explore HIV related stigma and self-disclosure in participants using questionnaires that we had developed and pilot-tested. The discussions were audio recorded, transcribed and translated. Using NVivo software package for qualitative analysis, we developed primary and secondary nodes and subsequent emergent themes.Results: We recruited 38 participants for the focus group discussions. Emergent themes were: types of disclosure, reasons for disclosure or non-disclosure, who was disclosed to and the reasons for disclosure, experienced stigma and resolving dissonance in non-disclosure.Conclusion: Our findings reveal HIV-related challenges for the elderly due to stigma and disclosure. There is need to combat this situation by normalizing societal expectations, roles and sexuality in the elderly as a way of fighting HIV/AIDS related stigma.Keywords: HIV, disclosure, elderly, enacted-stigma, anticipated-stigma, internalized-stigma